Lineage-Specific Growth Curves Document Large Differences in Response of Individual Groups of Marine Bacteria to the Top-Down and Bottom-Up Controls - Fecskeová, Lívia K; Piwosz, Kasia; Šantić, Danijela; Šestanović, Stefanija; Tomaš, Ana Vrdoljak; Hanusová, Martina; Šolić, Mladen; Koblížek, Michal (mSystems, 2021)
Marine bacterioplankton represent a diverse assembly of species differing largely in their abundance, physiology, metabolic activity, and role in microbial food webs. To analyze their sensitivity to bottom-up and top-down controls, we performed a manipulation experiment where grazers were removed, with or without the addition of phosphate. Using amplicon-reads normalization by internal standard (ARNIS), we reconstructed growth curves for almost 300 individual phylotypes. Grazer removal caused a rapid growth of most bacterial groups, which grew at rates of 0.6 to 3.5 day-1, with the highest rates (>4 day-1) recorded among Rhodobacteraceae, Oceanospirillales, Alteromonadaceae, and Arcobacteraceae. Based on their growth response, the phylotypes were divided into three basic groups. Most of the phylotypes responded positively to both grazer removal as well as phosphate addition. The second group (containing, e.g., Rhodobacterales and Rhizobiales) responded to the grazer removal but not to the phosphate addition. Finally, some clades, such as SAR11 and Flavobacteriaceae, responded only to phosphate amendment but not to grazer removal. Our results show large differences in bacterial responses to experimental manipulations at the phylotype level and document different life strategies of marine bacterioplankton. In addition, growth curves of 130 phylogroups of aerobic anoxygenic phototrophs were reconstructed based on changes of the functional pufM gene. The use of functional genes together with rRNA genes may significantly expand the scientific potential of the ARNIS technique. IMPORTANCE Growth is one of the main manifestations of life. It is assumed generally that bacterial growth is constrained mostly by nutrient availability (bottom-up control) and grazing (top-down control). Since marine bacteria represent a very diverse assembly of species with different metabolic properties, their growth characteristics also largely differ accordingly. Currently, the growth of marine microorganisms is typically evaluated using microscopy in combination with fluorescence in situ hybridization (FISH). However, these laborious techniques are limited in their throughput and taxonomical resolution. Therefore, we combined a classical manipulation experiment with next-generation sequencing to resolve the growth dynamics of almost 300 bacterial phylogroups in the coastal Adriatic Sea. The analysis documented that most of the phylogroups responded positively to both grazer removal and phosphate addition. We observed significant differences in growth kinetics among closely related species, which could not be distinguished by the classical FISH technique.
Keywords: phosphorus limitation; growth rate; amplicon sequencing; top-down control; growth curves; manipulation experiment; bacterioplankton; aerobic anoxygenic phototrophs; grazing